"The Distant Early Warning System": The Online Public Sphere and the Contemporary Artistic Movement in Saudi Arabia. Issue 2 (December 2019) - Foley, Sean
Abstract: "Social media, " Saudi artist Abdullah al-Shehri (known as Shaweesh) observes, is the "best tool we have available to showcase and express our art, " because it allows millions of Saudis to share and comment on a given work of art simultaneously. Building on this insight, this essay argues that Saudi artists, who have among the largest followings on the country's social media, have used the online public sphere to build a new social movement. They have adopted a role akin to Antonio Gramsci's concept of organic intellectuals – namely, men and women who are not part of the traditional intellectual elite, but who, through the language of culture, articulate feelings and experiences the masses cannot easily express. To paraphrase Ezra Pound, Saudi artists are the "antennae" of the kingdom's society, whose work is not "mere self-expression, " but, in the words of Marshall McLuhan, the "distant early warning system that can always be relied upon to tell the old culture what is beginning to happen to it." As a leading Saudi artist Abdulnasser Gharem observed in June 2019, "people need to listen to the artist."